2021
DOI: 10.1155/2021/6672444
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Model that Predicts the Risk of Diabetic Nephropathy in Type 2 Diabetes Mellitus Patients: A Retrospective Study

Abstract: Objective. To construct a novel nomogram model that predicts the risk of diabetic nephropathy (DN) incidence in Chinese patients with type 2 diabetes mellitus (T2DM). Methods. Questionnaire surveys, physical examinations, routine blood tests, and biochemical index evaluations were conducted on 1095 patients with T2DM from Guilin. A least absolute contraction selection operator (LASSO) regression and multivariable logistic regression analysis were used to screen out DN risk factors. A logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(21 reference statements)
1
1
0
Order By: Relevance
“… 29 , 30 A retrospective study conducted in Guilin, China, found that BUN was strongly associated with an increased risk of DN in patients with type 2 DM and found that increased Scr levels also increased the risk of DN progression. 31 Our result confirms that BUN and Scr are risk factors for DN in T2DM patients. This is similar to the results of previous studies, suggesting that BUN and Scr are risk factors for DN.…”
Section: Discussionsupporting
confidence: 85%
“… 29 , 30 A retrospective study conducted in Guilin, China, found that BUN was strongly associated with an increased risk of DN in patients with type 2 DM and found that increased Scr levels also increased the risk of DN progression. 31 Our result confirms that BUN and Scr are risk factors for DN in T2DM patients. This is similar to the results of previous studies, suggesting that BUN and Scr are risk factors for DN.…”
Section: Discussionsupporting
confidence: 85%
“…The most contributions came from scholars in Jiangsu Province, with a total of seven studies ( 18 , 20 , 28 , 30 , 38 , 40 , 41 ). The earliest studies were published in 2017 ( 35 , 40 ), and there were 23 studies published in the last three years ( 18 , 20 , 21 , 23 – 32 , 35 , 37 39 , 41 , 43 , 45 , 46 ). In terms of study types, there were 10 case–control studies ( 16 , 17 , 21 , 24 , 25 , 30 , 33 , 36 , 45 , 47 ), 5 cross-sectional studies ( 19 , 22 , 34 , 35 , 39 ), and 16 cohort studies ( 18 , 20 , 23 , 27 29 , 31 , 32 , 37 , 38 , 40 , 41 , 43 , 44 , 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies ( 20 , 23 , 24 , 27 , 31 34 , 36 38 , 40 , 42 , 44 , 45 , 47 ) consider hypertension a predictive factor for the risk of diabetic nephropathy in patients with type 2 diabetes. Sustained high blood pressure increases the burden on the kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under the ROC curve (AUC) was 0.813, and the C index of internal verification was 0.796. Decision curve analysis showed the risk profile of DN was clinically appropriate when the risk threshold ranged from 1% to 83% [ 25 ]. These two studies show that nomograms play a certain role in the risk assessment of DN.…”
Section: Discussionmentioning
confidence: 99%